Electron beam grafted Polyethylene/Polypropylene fibers: a novel approach to amine-functionalized adsorbents for Naproxen removal - Yusoff, Nor Aida; Abdullah, Luqman Chuah; Md. Jamil, Siti Nurul Ain; Ting, Teo Ming; Zainuddin, Halimatun Sakdiah (Elsevier, 2024)
In this study, polyethylene/polypropylene (PE/PP) was grafted with glycidyl methacrylate (GMA) and functionalized with two aliphatic amines. The objective of this study was to evaluate the efficacy of different amines in removing naproxen from water by comparing the influence of their alkyl chain lengths on interactions with naproxen. GMA was grafted onto PE/PP using electron beam irradiation to produce (PE/PP)-g-GMA. The grafting yields attained were 50 %, 147 %, 220 %, and 380 % by modifying the reaction time with an absorbed dose of 30 kGy. The grafted polymer was modified with ethylenediamine (EDA) and 1,3-diaminopropane (DAP) by varying the grafting yield, reaction time, and amine-to-isopropanol ratio. At 50 % amine ratio, 220 % grafting yield, and a reaction time of 3 hours, EDA and DAP achieved amine densities of 3.05 mmol/g and 2.87 mmol/g, respectively. FTIR and XPS analyses confirmed the successful grafting and amination of the PE/PP matrix with the integration of the epoxy groups and aliphatic amines. TGA revealed that the functionalized adsorbent remained thermally stable up to 200 ◦C and XRD confirmed the preservation of the PE/PP backbone structure. Notably, even at a low amine-to-isopropanol ratio (30 %) using EDA, the adsorbents achieved a high naproxen removal rate of 96.90 % within 90 min and an adsorption capacity of 247.10 mg/g, surpassing the performance of the DAP-modified (PE/PP)-g-GMA. These findings suggest that amine-functionalized adsorbents with short alkyl chain lengths exhibit higher removal efficiencies, as they are capable of reducing the residual concentration after adsorption to levels approaching the predicted no-effect concentration.